2008
DOI: 10.1158/1078-0432.ccr-08-0432
|View full text |Cite|
|
Sign up to set email alerts
|

Validation of a Standardized Method for Enumerating Circulating Endothelial Cells and Progenitors: Flow Cytometry and Molecular and Ultrastructural Analyses

Abstract: Purpose: Antigenic overlap among circulating endothelial cells (CEC) and progenitors (CEP), platelets, and other blood cells led to the need to develop a reliable standardized method for CEC and CEP quantification. These cells are emerging as promising preclinical/clinical tools to define optimal biological doses of antiangiogenic therapies and to help stratify patients in clinical trials. Experimental Design: We report the experimental validation of a novel flow cytometry method that precisely dissects CEC/CE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
143
3
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 150 publications
(158 citation statements)
references
References 22 publications
10
143
3
2
Order By: Relevance
“…The combination of Syto16 and 7AAD was used to gain insight into PPC viability according to van der Pol et al 13,14 Necrotic cells were identified as Syto16low/7AADþ, apoptotic cells as Syto16low/7AADÀ and viable cells as Syto16bright/7AADÀ.…”
Section: Flow Cytometrymentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of Syto16 and 7AAD was used to gain insight into PPC viability according to van der Pol et al 13,14 Necrotic cells were identified as Syto16low/7AADþ, apoptotic cells as Syto16low/7AADÀ and viable cells as Syto16bright/7AADÀ.…”
Section: Flow Cytometrymentioning
confidence: 99%
“…Sections were analyzed with a Philips CM-10 or a FEI Tecnai 12G2 electron microscopes (Einhdoven, the Netherlands). 13,15 Molecular characterization of sorted PPCs…”
Section: Electron Microscopy Characterization Of Sorted Ppcsmentioning
confidence: 99%
“…These conflicting results may be explained by the very limited number of patients analyzed, as well as different markers, used for enumerating EPC (Table 3). Accordingly, a recent report by Mancuso et al [54], who used a more standardized method, with limited intrareader and interreader variability, showed more EPC in metastatic breast cancers than locally advanced ones. Interestingly, in patients with pediatric solid malignancies, including medulloblastoma, neuroblastoma, sarcoma, and lymphomas [59], the levels of circulating bone marrow-EPC were found to be significantly higher, compared to no metastatic diseases.…”
Section: Clinical Applications: Epc As Biomarker and Therapeutic Target?mentioning
confidence: 99%
“…In light of the aforementioned results, showing the role of EPC in mammary tumor angiogenesis in animal models, [51,52] and in breast cancer patients [53,54]. As shown in Table 3, 3 of 6 studies failed to show significant difference in EPC among varying stages of breast cancer [53,55,56].…”
Section: Clinical Applications: Epc As Biomarker and Therapeutic Target?mentioning
confidence: 99%
“…As a result, FCM has become the gold standard to characterize clinical grade cell preparations in several fields of regenerative medicine. In our own laboratories, it has allowed the identification of rare stem cells and progenitors in peripheral blood and parenchymal tissues (12)(13)(14), thus prompting us to refine FCM protocols for liver stem cell analysis with a view to future clinical applications.…”
mentioning
confidence: 99%